KADAR KALSIUM DAN FOSFOR DARAH PADA TIKUS YANG DIBERIKAN MOCAF TERFORTIFIKASI KALSIUM DARI CANGKANG TELUR AYAM RAS - Wulandari Meikawati; Agus Suyanto (Universitas Muhammadiyah Semarang, 2015)
The most high calcium requirement occurs in adolescence than other age stages due to the rapid skeletal growth. The intake of calcium can be obtained from high-calcium foods or food ingredients that have been fortified with calcium. Mocaf is a product of flour from cassava (Manihot esculenta Crantz) is processed with the principle of modified cassava cell fermentation so that it has the color whiter than usual cassava flour and neutral flavor. Shell eggs is one of waste containing calcium is high enough, so that it can be used as fortifikan. This study aims to determine the levels of calcium and phosphorus in the blood of rats given standard feed ingredients coupled with mocaf fortified with calcium from the shells of eggs. Experimental animals divided into four, namely group 1 was given a standard feed (control group), group 2 was given a standard feed + mocaf fortified calcium from eggshell with a dose of 5%, group 3 was given a standard feed + mocaf fortified calcium from eggshell with a dose of 10% Group 4 was given the standard feed + CaCO3 at a dose of 5%. Treatment was given for 7 weeks. Blood sampling performed on the first and eighth week. The results showed the highest rates of blood calcium levels before treatment contained in the group 2 is 10.31 mg / dl and the lowest 9,78mg / dl in group 1. After the treatment is given the highest rates of blood calcium levels found in the group 3 is 12.04 mg / dl and the lowest 9.95 mg / dl in group 1. There is the effect of calcium on the eggshell of the blood calcium level, and there are differences in the level of calcium in the blood before and after treatment. There are differences in phosphorus levels before and after treatment, but there was no difference between treatment groups phosphorus levels.Keywords: Calcium, Phosphorus, Rats, MOCAF